Bilateral generic working memory circuit requires left-lateralized addition for verbal processing. - Ray, M; Mackay, C; Harmer, C; Crow, T (2008)
According to the Baddeley-Hitch model, phonological and visuospatial representations are separable components of working memory (WM) linked by a central executive. The traditional view that the separation reflects the relative contribution of the 2 hemispheres (verbal WM--left; spatial WM--right) has been challenged by the position that a common bilateral frontoparietal network subserves both domains. Here, we test the hypothesis that there is a generic WM circuit that recruits additional specialized regions for verbal and spatial processing. We designed a functional magnetic resonance imaging paradigm to elicit activation in the WM circuit for verbal and spatial information using identical stimuli and applied this in 33 healthy controls. We detected left-lateralized quantitative differences in the left frontal and temporal lobe for verbal > spatial WM but no areas of activation for spatial > verbal WM. We speculate that spatial WM is analogous to a "generic" bilateral frontoparietal WM circuit we inherited from our great ape ancestors that evolved, by recruitment of additional left-lateralized frontal and temporal regions, to accommodate language.